2021
DOI: 10.1017/s0047279421000313
|View full text |Cite
|
Sign up to set email alerts
|

First step and last resort: One-Euro-Jobs after the reform

Abstract: Job creation programmes aim at increasing the employability of hard-to-place unemployed, and eventually integrating them into employment. Yet, previous evaluation studies have been pessimistic about their efficacy. For One-Euro-Jobs, a job creation programme for welfare benefit recipients in Germany, previous evaluations found unfavourable effects particularly for easier-to-place participants. Thus, in 2012 the legislator reformed the programme in order to target the hard-to-place more accurately. This study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…These considerations are in line with findings on the German workfare programme called One-Euro Jobs, which were more effective in sectors with high labour demand (Harrer and Stockinger (2021)). Especially, private placement services might have better contact to firms in specific sectors.…”
Section: Discussionsupporting
confidence: 84%
“…These considerations are in line with findings on the German workfare programme called One-Euro Jobs, which were more effective in sectors with high labour demand (Harrer and Stockinger (2021)). Especially, private placement services might have better contact to firms in specific sectors.…”
Section: Discussionsupporting
confidence: 84%
“…Workfare jobs are often located in sectors with low labour demand, which can limit the utility of work experience gained there (Harrer and Stockinger, 2021). Nonetheless, workfare might provide a first step into the labour market, for instance by providing an opportunity to become accustomed to a regular work schedule, and may therefore have positive effects on subsequent regular employment for people with low employment experience.…”
Section: Institutional Settingmentioning
confidence: 99%
“…Previous research has found active labour market programmes such as short training, further vocational training and workfare to vary in their ability to improve employment opportunities, with the greatest positive effects for further vocational training and lowest effects for workfare (Bernhard, 2016;Harrer et al, 2020;Harrer and Stockinger, 2021). Dengler (2019) finds that positive job quality effects are particularly evident for further vocational training.…”
Section: Institutional Settingmentioning
confidence: 99%
“…Access is limited to those with least employment prospects. Welfare recipients are sanctioned if they refuse a One Euro Job offer, while work is limited to part-time work so that participants can spend the remainder of their working week on job search requirements (Hohmeyer and Wolff, 2010; Harrer and Stockinger, 2021).…”
Section: The Evolution Of Activation and The Demise Of Job Creationmentioning
confidence: 99%